Correlation of History and Eschatology in Christian Historiosophy - Sołga, Przemysław (Sensus Historiae, 2021)
In Christian philosophy of history the idea of grand historical narrative is correlated with eschatology, i.e. theological teachings about the final destiny of man and mankind, while secular history is directly linked with the history of salvation. This article discusses issues such as the temporal character of history in relation to eschatology and its chosen aspects. The Bible, official church doctrine, and the writings of diverse Christian thinkers and theologians serve as points of reference. Different elements are taken into account, such as the temporal and theological dimension of human death, the end of the world, and the afterlife, supposed to unveil itself in the final times through the omnipresence of the “Kingdom of God,” with the latter anticipated in the daily struggles of our modern lives.